(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2021)
Exploring new forms of socialization by creating artwork in transformation, reinventing communication, is the goal of HugForUs. Amedani, the author, becomes a creator of tools, providing technological devices that make the forms of design and participation accessible to all, towards a collective pro- cess of creation. The redefinition of space, through collective action, widening the possibilities of the user, allows invisible identities to appear in the visible. The project triggers an active process that goes from individual to collective in a continuous semantic and aesthetic evolution, extending the capabilities of the subject-user. Overcoming the object-art identifier through public actions that exploit online platforms. The operation is defined, using the words of Giacomo Verde, as a «artwork of relationship between people». Amedani was able to activate creative contexts that allow the different processes of relationship.